2001
DOI: 10.1161/hc2901.094150
|View full text |Cite
|
Sign up to set email alerts
|

Independent Association Between Plasma Leptin Levels and Heart Rate in Heart Transplant Recipients

Abstract: Background-Leptin, the protein product of the ob gene, has been linked to a faster heart rate in animal and human studies.The interaction between leptin and heart rate in the denervated heart is not known. Therefore, we studied the relationship between plasma leptin levels and heart rate in heart transplant recipients. Methods and Results-We studied 32 male patients (mean age, 56.5Ϯ9.3 years; range, 41 to 74 years) after orthotopic heart transplantation. All subjects underwent a physical examination, anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
(29 reference statements)
1
23
0
4
Order By: Relevance
“…Such a relationship may be transposed into a direct correlation between left ventricular size and plasma leptin levels. While it seems reasonable that the higher heart rate under hyperleptinemia may be due to leptin-induced sympathetic activation, an independent association between leptin levels and heart rate was observed in heart transplant recipients with sympathetic denervation (Winnicki et al 2001). This finding suggests a direct effect of leptin on heart rate conceivably through cardiac leptin receptors, although direct effects of leptin on the cardiac conducting system and cardiac growth still warrant further study.…”
Section: Leptin Heart Rate and Cardiac Functionmentioning
confidence: 89%
“…Such a relationship may be transposed into a direct correlation between left ventricular size and plasma leptin levels. While it seems reasonable that the higher heart rate under hyperleptinemia may be due to leptin-induced sympathetic activation, an independent association between leptin levels and heart rate was observed in heart transplant recipients with sympathetic denervation (Winnicki et al 2001). This finding suggests a direct effect of leptin on heart rate conceivably through cardiac leptin receptors, although direct effects of leptin on the cardiac conducting system and cardiac growth still warrant further study.…”
Section: Leptin Heart Rate and Cardiac Functionmentioning
confidence: 89%
“…There may be various reasons why these allometric relationships would differ from theoretical predictions derived from fractal models, including deviations from model theoretical assumptions, differences in the metabolic rates of different tissues (which may vary systematically with body size even within normal ranges of body weight) and the effects of various neurohormonal pathways that may exert direct distant effects on the heart and vasculature independently of local flow phenomena. For example, leptin secreted by adipocytes bears a strong relationship with body weight and is known to affect heart rate both through direct effects on the heart26 and through autonomic regulation. This heart-rate increasing effect would be expected to counterbalance the strong and highly non-linear negative relationship between body mass and heart rate that would be predicted purely on the basis of from fractal-network theory 25, 26…”
Section: Discussionmentioning
confidence: 99%
“…For example, leptin secreted by adipocytes bears a strong relationship with body weight and is known to affect heart rate both through direct effects on the heart26 and through autonomic regulation. This heart-rate increasing effect would be expected to counterbalance the strong and highly non-linear negative relationship between body mass and heart rate that would be predicted purely on the basis of from fractal-network theory 25, 26…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has been associated with impaired fibrinolysis [6,7], hypertension [8] and calcification of vascular cells [9]. In addition, plasma leptin concentrations are raised in patients with congestive heart failure [10] and correlate with heart rate in heart transplant recipients [11]. Moreover, some authors have proposed hyperleptinemia as a component of a metabolic syndrome of cardiovascular risk [12] while others have shown that leptin is an independent risk factor for coronary events in hypercholesterolemic men [13].…”
Section: Introductionmentioning
confidence: 99%